2011
DOI: 10.1007/s12665-011-0977-0
|View full text |Cite
|
Sign up to set email alerts
|

Wave climate and morphosedimentary characteristics of the Kenitra–Bouknadel sandy coast, Morocco

Abstract: The Bouknadel-Kenitra 20-km sandy coastline is of strong interest from the perspectives of beach amenity, tourism and erosion issues. This section of the Moroccan coastline has only received little attention in the literature so far and morphosedimentary characteristics as well as wave climate are poorly understood. The present paper provides the first extensive description of both wave climate and alongshore variability in the morphosedimentary behavior of these wave-dominated beaches, combined with accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…This research reveals that most of the study area is in accretion (286000 m²/year) while the net rate of erosion is around À 374 m²/ year. Our results, combined with the earlier study of Hakkou et al (2011), show steady seaward migration of the shoreline at Chlihat of the order of 1.4 m/year. The results exhibit good agreement with values by EPR and LR models where the back calculated RMSE error is 6.4 m.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…This research reveals that most of the study area is in accretion (286000 m²/year) while the net rate of erosion is around À 374 m²/ year. Our results, combined with the earlier study of Hakkou et al (2011), show steady seaward migration of the shoreline at Chlihat of the order of 1.4 m/year. The results exhibit good agreement with values by EPR and LR models where the back calculated RMSE error is 6.4 m.…”
Section: Resultssupporting
confidence: 84%
“…In contrast, Chlihat beach north of the Sebou estuary exhibits a dissipative shape with spilling breakers and experiences accretion due to the littoral drift. The net longshore drift averaged over the 8-year period at Chlihat beach, Sidi Boughaba beach and Nations beach is found to be southward and about 85,000, 340,000 and 200,000 m 3 /year, respectively (Hakkou et al, 2011). Deepika et al (2014) showed the same trend on the Udupi coast, western India, where sandy beaches are subjected to erosion due to migration of the river mouth after the construction of breakwaters in the 1980s on either side of the Udyavaraestuary.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations